WRKY Transcription Factor OsWRKY29 Represses Seed Dormancy in Rice by Weakening Abscisic Acid Response - Zhou, Chunlei; Lin, Qibing; Lan, Jie; Zhang, Tianyu; Liu, Xi; Miao, Rong; Mou, Changling; Nguyen, Thanhliem; Wang, Jiachang; Zhang, Xiao; Zhou, Liang; Zhu, Xingjie; et al. (Frontiers in Plant Science, 2020)
For efficient plant reproduction, seed dormancy delays seed germination until the environment is suitable for the next generation growth and development. The phytohormone abscisic acid (ABA) plays important role in the induction and maintenance of seed dormancy. Previous studies have identified that WRKY transcription factors can regulate ABA signaling pathway. Here, we identified an Oswrky29 mutant with enhanced dormancy in a screen of T-DNA insertion population. OsWRKY29 is a member of WRKY transcription factor family which located in the nuclear. The genetic analyses showed that both knockout and RNAi lines of OsWRKY29 had enhanced seed dormancy whereas its overexpression lines displayed reduced seed dormancy. When treated with ABA, OsWRKY29 knockout and RNAi lines showed greater sensitivity than its overexpression lines. In addition, the expression levels of ABA positive response factors OsVP1 and OsABF1 were higher in the OsWRKY29 mutants but were lower in its overexpression lines. Further assays showed that OsWRKY29 could bind to the promoters of OsABF1 and OsVP1 to inhibit their expression. In summary, we identified a new ABA signaling repressor OsWRKY29 that represses seed dormancy by directly downregulating the expression of OsABF1 and OsVP1.